CO01 | Statin therapy for the prevention of venous thromboembolism in cancer patients: a systematic review and meta-analysis (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Venous thromboembolism (VTE) in cancer patients might produce severe clinical consequences such as anticancer therapies delay, hospitalization, and increased risk of both thrombotic recurrence and bleeding during anticoagulant therapy; moreover, in these patients, VTE is the second leading cause of death after cancer itself, reducing overall survival rates. If previous studies already suggested a potential role of statins in preventing VTE in the general population, there is still paucity of evidence concerning statins’ effect in the prevention of cancer-associated thrombosis. This systematic review and meta-analysis aims at filling this gap, by evaluating statins’ role in VTE prevention in cancer patients.